The Characters In “The Pursuit Of Happyness” By Gabriella Muccino - Ulfa Rahma Dhini (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2023)
The goal of this study is to describe the focus of the research that consists of the characters in the film “The Pursuit of Happyness “by Gabriella Muccino. The data were taken based on the quotations that focus on the characters found in the film script and time sequence “The Story of My Life”. The research is analyzed by using the qualitative approach. The kind of characters is based on eight instruments, they are major, minor, protagonist, antagonist, flat, round, static, and dynamic. This study is conducted based on literature reviews by observing documents from the film. The film consists of 1 hour 57 minutes duration and 103 pages of the original script. The findings that are found based on the observation from this film were significant. The character instruments consist of Minor by 30% % at the highest position, then Protagonist by 20 %, static by 10 %, antagonist by 10 %, Dynamic by 10 %, Round by 10 %, and Major by 7 %. and flat by 3%. The conclusions showed that the character that emerged as the minor character that consists in this film makes this film more interesting. After analyzing this film, the writer concluded that this element emerged from the major character’s hard work and self-empowerment strength that builds the personal competence involving personal journey and process of understanding as the effect of many problems in his life.